The Role Of The Sub-District Government In Public Service Management For The Community In Muaradua Kisam Sub-District, South Ogan Komering Ulu Regency - Adi Ismul Mubaraq; Munajat, Munajat; Rini Efrianti; Kurnia, Dadang (SEAN Institute, 2024)
The Muaradua Kisam sub-district government as one of the government organizations, of course, also has the main task of providing civil services and public services for its community in addition to empowerment and development tasks. However, in the practice of government in the Muaradua Kisam sub-district in the previous period, there was a tendency for the sub-district government to prioritize development tasks over service tasks to the community. As a result, service tasks that should take precedence, are actually neglected while the implementation of development tasks has also not succeeded in improving welfare that satisfies the community fairly and evenly. This research method is a descriptive method with qualitative data analysis, with the aim of knowing the role of the government in organizing public service management and knowing the supporting and inhibiting factors in the implementation of government services in the muaradua kisam sub-district. The results showed that the role of the Muaradua Kisam sub-district government in the task of organizing public services in Muaradua Kisam sub-district is running well. However, human resources and service facilities are still a factor inhibiting these services. so that it is expected to improve or perfect the role of government in organizing public service tasks in the Muaradua Kisam sub-district, OKU Selatan Regency in the future.